Measurement of event data from text - Patrick T. Brandt; Marcus Sianan (Frontiers in Political Science)
We examine measurement concerns about computer-aided political event data in the state-of-the-art after 2015. The focus is on how to compare and quantify the mathematical and/or conceptual distance between what a machine codes/classifies from information describing an event and the actual circumstances of the event, or the ground truth. Three primary arguments are made: (1) It is important for users of event data to understand the measurement side of these data to avoid faulty inferences and make better decisions. (2) Avant-garde event data systems are still not free from some of the fundamental problems that plague legacy systems (investigated are theoretical and real-world examples of measurement issues, why they are problematic, how they are dealt with, and what is left to be desired even with newer systems). (3) One of the most crucial goals of event data science is to attain congruence between what is machine-coded/classified vs. the ground truth. To support these arguments, the literature is benchmarked against well-documented sources of measurement error. Guidance is provided on how to make performance comparisons within and across language models, identify opportunities to improve event data systems, and more articulately discuss and present findings in this area of research.